Crossed-beam energy transfer: polarization effects and evidence of saturation. (5th April 2018) - Turnbull, D; Colaïtis, A; Follett, R K; Palastro, J P; Froula, D H; Michel, P; Goyon, C; Chapman, T; Divol, L; Kemp, G E; Mariscal, D; Patankar, S; et al.
Abstract: Recent results on crossed-beam energy transfer are presented. Wavelength tuning was used to vary the amount of energy transfer between two beams in a quasi-stationary plasma with carefully controlled conditions. The amount of transfer agreed well with calculations assuming linear ion acoustic waves (IAWs) with amplitudes up to δ n / n ≈ 0.015 . Increasing the initial probe intensity to access larger IAW amplitudes for otherwise fixed conditions yields evidence of saturation. The ability to manipulate a beam's polarization, which results from the anisotropic nature of the interaction, is revisited; an example is provided to demonstrate how polarization effects in a multibeam situation can dramatically enhance the expected amount of energy transfer.